Marking time in the Golden State : women's imprisonment in California - Kruttschnitt, Candace (Cambridge studies in criminology (Cambridge University Press), 2005)
"In recent decades, the nature of criminal punishment has undergone profound change in the United States. This case study of women serving time in California in the 1960s and 1990s examines two key points in this recent history. The authors begin with a look at imprisonment at the California Institution for Women in the early 1960s, when the rehabilitative model dominated official discourse. To this they compare women's experiences in the 1990s, at bot the California Institution for Women and the Valley State Prison for Women, when the recent "get tough" era was near its peak.